Effects of age condition on the distribution and integrity of inorganic fillers in dental resin composites - D'Alpino, Paulo Henrique Perlatti; Svizero, Nádia da Rocha; Bim Júnior, Odair; Valduga, Claudete Justina; Graeff, Carlos Frederico de Oliveira [UNESP]; Sauro, Salvatore (Springer, 2015)
The aim of this study is to evaluate the distribution of the filler size along with the zeta potential, and the integrity of silane-bonded filler surface in different types of restorative dental composites as a function of the material age condition. Filtek P60 (hybrid composite), Filtek Z250 (small-particle filled composite), Filtek Z350XT (nanofilled composite), and Filtek Silorane (silorane composite) (3M ESPE) were tested at different stage condition (i.e., fresh/new, aged, and expired). Composites were submitted to an accelerated aging protocol (Arrhenius model). Specimens were obtained by first diluting each composite specimen in ethanol and then dispersed in potassium chloride solution (0.001 mol%). Composite fillers were characterized for their zeta potential, mean particle size, size distribution, via poly-dispersion dynamic light scattering. The integrity of the silane-bonded surface of the fillers was characterized by FTIR. The material age influenced significantly the outcomes; Zeta potential, filler characteristics, and silane integrity varied both after aging and expiration. Silorane presented the broadest filler distribution and lowest zeta potential. Nanofilled and silorane composites exhibited decreased peak intensities in the FTIR analysis, indicating a deficiency of the silane integrity after aging or expiry time. Regardless to the material condition, the hybrid and the small-particle-filled composites were more stable overtime as no significant alteration in filler size distribution, diameter, and zeta potential occurred. A deficiency in the silane integrity in the nanofilled and silorane composites seems to be affected by the material stage condition. The materials conditions tested in this study influenced the filler size distribution, the zeta potential, and integrity of the silane adsorbed on fillers in the nanofilled and silorane composites. Thus, this may result in a decrease of the clinical performance of aforementioned composites, in particular, if these are used after inappropriate storage conditions.
Keywords: Aging; Dynamic light scattering; Filler sizing distribution; Methacrylate; Resin composites; Silorane; Zeta potential